OFFER OF INTEGRATIVE AND COMPLEMENTARY PRACTICES IN PRIMARY CARE - Mendes Souza, Kamila; Dernier Martins, Luisilda Maria; dos Santos Mota, Joverlandia; Menezes Silva Prata , Kerley (Cadernos ESP, 2023)
This work is an experience report that seeks to describe and reflect on the promotion of care with the provision of integrative and complementary practices in a primary care unit located in a city of Ceará state. The offer of practices took place in the period from November 2020 to December 2021. Being initially developed four workshops with the health unit professionals in order to present the Integrative and Complementary Health Practices, the National Policy on Integrative and Complementary Practices, and elaborate the flow of care and user profile. Observations were noted in a field diary and then analyzed with the findings of the literature, resulting in reflections on the expansion of access to Integrative and Complementary Practices in the Unified Health System, the relevance in promoting complementary health care to users, the need for management support, valuing professionals and institutionalization of the policy.
Keywords: Complementary Therapies; Primary Health Care; Unified Health System